Comparative genomics of Botryosphaeria dothidea and B. kuwatsukai, causal agents of apple ring rot, reveals both species expansion of pathogenicity-related genes and variations in virulence gene content during speciation - Bo Wang; Xiaofei Liang; Mark L. Gleason; Rong Zhang; Guangyu Sun (IMA Fungus)
Abstract Ring rot, one of the most destructive diseases of apple worldwide, is caused primarily by Botryosphaeria dothidea and 8. kuwatsukai. Here, we sequenced the genomes of 8. dothidea strain PG45 (44.3 Mb with 5.12 % repeat rate) and 8. kuwatsukai epitype strain PG2 (48.0 Mb with 13.02 % repeat rate), and conducted a comparative analysis of these two genomes, as well as other sequenced fungal genomes, in order to understand speciation and distinctive patterns of evolution of pathogenicity-related genes. Pair-wise genome alignments revealed that the two species are highly syntenic (96.74 % average sequence identity). Both species encode a significant number of pathogenicity-related genes, e.g.carbohydrateactive enzymes (CAZYs), plant cell wall degrading enzymes (PCWDEs), secondary metabolites (SMs) biosynthetic enzymes, cytochrome P450 enzymes (CYPs), and secreted peptidases, in comparison to all additional sequenced fungal species involved in various life-styles. The number of pathogenicity-related genes in 8. dothidea and 8. kuwatsukai is higher than other genomes of Botryosphaeriaceae pathogens (Macrophomina phaseolina and Neofusicoccum parvum), suggesting a secondary round of Botryosphaeria-lineage expansion in the family. There were, however, also significant differences in the genomes of the two Botryosphaeria species. Botryosphaeria kuwatsukai, which infects only apple and pear, apparently lost a set of SMs genes, CAZYs and PCWDEs, possibly as a result of host specialization. Botryosphaeria kuwatsukai contained significantly more transposable elements and higher value of repeat induced point (RIP) index than B. dothidea. Our results will be instrumental in understanding how both phytopathogens interact with their plant hosts and in designing efficient strategies for disease control and molecular breeding to help ensure global apple production and food security.